Analysis and Research on Pigment Precipitation of Eggshell Based on Green Environment-friendly Breeding Technology. Issue 5 (January 2021) - Liao, Bing; Liu, Yinan; Cao, Jicheng; Ning, Zhonghua
Abstract: The development of poultry farming as a basic industry is driven by this form of development, and agricultural development technology has been greatly improved, which is of great significance for the development of agricultural production. It can be said that in this Under this new form of conditions, people's ideas have also undergone great changes. In the process of agricultural production development, one of the most important influencing factors is to promote the rapid development of poultry farming while also promoting Its stable, healthy and sustainable development. Therefore, it is an important task to achieve green and environmentally friendly farming in the poultry industry and promote the sustainable development of the poultry industry. This article will conduct a series of analyses on how to achieve green and environmentally friendly farming. At the same time, in order to explore the relationship between eggshell colour, composition and structure and eggshell quality, the paper selected 98 normal eggs produced by hens with green environmental protection, and then the quality of the eggshell was measured; then the eggshell colour was determined the instrument measures the colour of the eggshell and explores the deposition rule of the eggshell pigment. Then use the same batch of eggshells to determine the composition of the eggshells, and finally divide them into three groups of strong, medium and weak according to the strength of the eggshells. Take 5 eggshells in each group to observe the microstructure and crystal structure. The study found that the deposition law of eggshell pigments: biliverdin IX and protoporphyrin IX in the eggshell both reached the maximum secretion in the final stage of eggshell formation, and they may be regulated by the same factors. Eggshell colour has a certain relationship with egg weight, eggshell strength, eggshell thickness and Hastelloy unit.